Hypothermia in Children with Severe Malnutrition: Low Prevalence on the Tropical Coast of Kenya - Talbert, A; Atkinson, S; Karisa, J; Ignas, J; Chesaro, C; Maitland, K (Oxford University Press, 2009)
Hypothermia is stated as a common complication of severe malnutrition although there are little primary data to support this. We performed a prospective study of children with severe acute malnutrition (SAM) admitted to a district hospital in Kenya. We documented the prevalence of hypothermia and examined its association with outcome and ambient temperature. During a 2-year period 667 children were recruited. Hypothermia was recorded in only 12 out of 15 191 (0.08%) temperature observations and as a single event in 12 children (2% of cases). There was no correlation with ambient temperature. Although mortality rates were higher in children with hypothermia (4/12, 33%) than those without (121/655, 18%), the timing of hypothermia did not coincide with clinical deterioration. Hypothermia was a rare marker of severity in our setting. We recommend that other observations be highlighted to identify high risk groups and that routine temperature observations be reduced wherever staff are few.